PENGGANTIAN SEBAGIAN JAGUNG DENGAN TEPUNG BATANG PISANG GOROHO ( Musa acuminata, sp) DALAM RANSUM TERHADAP PERFORMANS BROILER - Manalip, Melinda O.; Najoan, M.; Imbar, M.R.; Kowel, Y.H.S. (ZOOTEC, 2018)
A study was aimed to evaluated the effect of partial replacement of corn with goroho banana stem mealon broiler chicken performans. The study was conducted at Faculity of Animal Science, University of Sam Ratulangi Manado. Using sixty three weeks broiler CP 707. Research used a complete randomized design, consisting of 4 treatmenst and 5 replications, ie  Ro : ration without goroho banana stem meal, R1 : 5% corn meal replaced with goroho banana stem meal, R2 : 10% corn meal replaced with goroho banana stem meal , R3 : 15% corn meal replaced with goroho banana stem meal . The variables which measured were : ration consumption, body weigth gain and ration conversion. The data were analyzed using analysis of variance ( Anova), and any significant differences were further test using Tukey test. The treatment was non significantly  diference ( P > 0,05) on ration consumption, but significantly difference ( P > 0,05 ) on body weight gain and ration conversion. The results of analysis of variance showed that the was non significantly difference (P>0.05) on ration consumption, while the addition of body weight and ration conversion were significantly difference ( P> 0,05 ). The Tukey test showed that the  body weight gain of R0 non significantly diference  ( P > 0,05 ) to the treatment  of R1 however R0  was significantly diference to R2 and R3, while the treatment of R1 with R2 and R1 with R3 showed significantly difference (P>0.05 )Based on this study, it could be conduded the Goroho banana stem meal (musa acuminata, sp) could substitute a part of corn up to 5% which made a better performance for broiler chicken Keywords : Broiler, Goroho banana steam meal, broiler performans